2014
DOI: 10.3390/molecules191118558
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Genistein Glycosides Inhibiting EGFR Phosphorylation Enhance the Effect of Radiation in HCT 116 Colon Cancer Cells

Abstract: The need to find new EGFR inhibitors for use in combination with radiotherapy in the treatment of solid tumors has drawn our attention to compounds derived from genistein, a natural isoflavonoid. The antiproliferative potential of synthetic genistein derivatives used alone or in combination with ionizing radiation was evaluated in cancer cell lines using clonogenic assay. EGFR phosphorylation was assessed with western blotting. Genistein derivatives inhibited clonogenic growth of HCT 116 cancer cells additivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Genistin has attracted much attention due to its wide variety of pharmacological activities, such as weak oestrogen activity [1], antioxidant activity [2,3], hemolysis activity and antibacterial activity [4]. It is also considered as an effectual preventive for breast cancer [5], colon cancer [6], osteoporosis [7] and so on. Therefore, Genistin is often used as dietary supplements [8].…”
Section: Introductionmentioning
confidence: 99%
“…Genistin has attracted much attention due to its wide variety of pharmacological activities, such as weak oestrogen activity [1], antioxidant activity [2,3], hemolysis activity and antibacterial activity [4]. It is also considered as an effectual preventive for breast cancer [5], colon cancer [6], osteoporosis [7] and so on. Therefore, Genistin is often used as dietary supplements [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies illustrated that some Chinese herbal monomers, such as curcumin, icariin, and genistein derivatives, enhance radiosensitivity in HT29 and HCT116 cells. 21 23 …”
Section: Discussionmentioning
confidence: 99%
“…And oral genistein could also inhibit distant metastasis formation and suppressed neo-angiogenesis in transplanted tumors [6]. In addition, it has been reported that the anti-tumor effects of genistein on CRC also involved with suppression WNT, NF-κB cell Signaling pathway, and modulation of apoptotic gene Bcl-2, Box, EGFR, and ROS [16,25,26,27]. Those findings suggested that genistein possesses effectively anti-cancer effects on CRC without any visible toxicity through the regulation of several signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that genistein inhibits human colon cancer cell Caco2 migration, accompanied with decrease of Akt phosphorylation, suggesting that suppression of the Akt signaling pathway may involved in the anti-tumor effects of genistein in CRC [14]. In addition, other tumor-related factors, such as FLT4 [6], estrogen receptor (ER) β [15], and EGFR [16] have also been demostreated to participate in the anti-proliferation and apoptosis-induced effects of genistein on CRC. However, the roles and potential mechanisms of genistein in CRC are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%